Systemic inflammation and the risk of adverse clinical outcomes in heart failure with preserved ejection fraction - Chi Nguyen; Guanghao Zhang; Prashanth Iyer; Amanda Ackermann; Jeffrey R. Skaar; Wing Chow; Radha Ryali; Josephine Harrington (Frontiers in Cardiovascular Medicine, 2026)
Introduction Systemic inflammation is implicated in the pathogenesis of cardiovascular disease, including heart failure (HF). We examined the association between systemic inflammation, indicated by elevated high-sensitivity C-reactive protein (hsCRP), and adverse clinical outcomes in individuals with HF with preserved ejection fraction (HFpEF). Methods This retrospective cohort study identified individuals with HFpEF from the Komodo Healthcare Map™ database (01/01/2016 to 12/31/2023) using a validated algorithm. Systemic inflammation status was established by hsCRP testing: with systemic inflammation if ≥1 hsCRP value of 2-10 mg/L and without systemic inflammation if all hsCRP values <2 mg/L. The relationship between hsCRP and risk for HF events, including all-cause mortality, HF hospitalization and urgent HF visits was examined using Cox proportional hazards models with multivariable adjustment. Results A total of 11,015 individuals with HFpEF and a qualifying hsCRP measurement were identified (mean age 66.4 years; 44% with systemic inflammation). The incidence rate of the composite HF endpoint was 103.2 per 1,000 person-years for those with systemic inflammation versus 83.3 for those without. Systemic inflammation was associated with a 21% increased risk of the composite HF endpoint (HR 1.21, 95% CI 1.11-1.31). Systemic inflammation was associated with increased risk of HF hospitalization (HR 1.17, 95% CI 1.03-1.33) and urgent HF visits (HR 1.21, 95% CI 1.08-1.35) but not all-cause mortality (HR 1.14, 95% CI 0.98-1.32). Conclusion Systemic inflammation was associated with increased risk of future adverse CV-related outcomes in individuals with HFpEF, highlighting unmet clinical needs for this population and the potential to optimize their care.